AerospaceLab Journal 2018
DOI: 10.12762/2018.al14-06
|View full text |Cite
|
Sign up to set email alerts
|

On the Validation and Use of High-Fidelity Numerical Simulations for Gust Response Analysis

Abstract: Aeroelasticity and Structural DynamicsOn the Validation and Use of High-Fidelity Numerical Simulations for Gust Response Analysis S pecific gust response is considered as one of the most important loads encountered by an aircraft. The Certification Specification (CS) 25, defined by the European Aviation Safety Agency (EASA), and the Federal Aviation Regulations (FAR) 25, defined by the Federal Aviation Administration (FAA), describe the critical gusts that an aircraft must withstand. They must be analyzed for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…They concluded that the structural weight saving was mainly limited by the allowed load factors considered in such optimization, the finite control authority of the actuators, and the achievable reliability of the GLA system itself. Huvelin et al [4] conducted a numerical simulation for the gust response along with experimental results at ONERA to present a gust load alleviation study. Numerical comparisons were performed using various techniques of gust modeling and finally, an application example for gust load alleviation was presented.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the structural weight saving was mainly limited by the allowed load factors considered in such optimization, the finite control authority of the actuators, and the achievable reliability of the GLA system itself. Huvelin et al [4] conducted a numerical simulation for the gust response along with experimental results at ONERA to present a gust load alleviation study. Numerical comparisons were performed using various techniques of gust modeling and finally, an application example for gust load alleviation was presented.…”
Section: Introductionmentioning
confidence: 99%